(untitled) (Research, Society and Development, 2021)
The cumbaru also known in some regions as baru, cumbaru, barujo, coco-beans or cumaru is a species widely distributed in the country. The wood is high density and durable, and both the fruit pulp and seeds are edible, attracting a diverse fauna of mammals and insects. Due to the great exploitation of its wood and mainly because it is a source of food, the fruit of cumbaru is increasingly difficult to find. With this, the aim of this work was to establish the ideal harvest period through the physiological maturation of cumbaru seeds, through the physiology and biometry of fruits and seeds. The fruits were collected from the trees, 180, 225 and 275 days after the anthesis (DAA). The experimental design used was the one entirely randomized in a 3x3 factorial scheme (three lots and three collection periods) with four repetitions, being considered 40 fruits per repetition. Morphological characteristics of the fruits and seeds were evaluated (longitudinal length, width, thickness, fresh weight and volume) and physical and physiological characteristics of the seeds such as: water content, germination, first germination count, germination speed index and weight of one thousand seeds. It was observed, along the collection periods, increasing values for the fruit and seed variables, the best physiological quality was observed during the 2nd and 3rd collection periods.